Optimization of employee scheduling using linear programming model / Nur Hidayah Fakhrurrazi & Nurzawiyah Noorzaimi - Fakhrurrazi, Nur Hidayah; Noorzaimi, Nurzawiyah (2019)
Every company want to minimize the number of their employee in order to reduce the cost while maintaining their production. This can be done by rearranging the employees’ shifts in the current schedule. There are many ways to optimize schedule in business operation. One of the best way to be use is the linear programming (LP) method which is easier to apply in minimizing the number of employees needed by the company. An LP model will be set up based on the minimum workers number needed in a shift and there are two types of shift discussed which are daily shift and time shift. Other than that, LP is also used to achieve the target cost when minimizing the company’s employee. The LP models are solved by using Maple and Lingo software where the minimum number of employees needed will be sorted out according to the starting day of their shift.